Management of Higher Education via Integration of Business and Science - Abilov, S. M. (Journal of Economic Research & Business Administration, 2016)
The goal of the research is to demonstrate management in higher education via integration of business and science. Methodology: in the research, the general cognition methods – observation, deduction, and induction, descriptive and comparative analysis – are applied. Novelty/Significance of the research: a profound analysis of higher education system management in the aspect of its integration with business and science has been conducted (management approaches and methods, and review of international experience). Higher education institution management and its integration with business and science provide the system of professional training, which will enable graduates to contribute to the improvement in the society, economy, business, science and development of new technologies. The results of the research: graphs, demonstrating the role of higher education institutions in innovation, social partnership benefits, the functioning of higher education, business, and science integration system, which, in general, show integration links of education, business and science, have been developed.